A single camera 360‐degree real time vision‐based localization method with application to mobile robot trajectory tracking. Issue 3 (30th May 2021) - Singhirunnusorn, Khomsun; Fahimi, Farbod; Aygun, Ramazan
Abstract: A method is proposed for real‐time vision‐based localization in the 360° area around a three‐dimensional (3D) reference object with a single camera. The problem is split into three subproblems. First, 360° 3D object recognition is proposed, in which a computer vision solution can recognize a reference object from all possible 360° locations. Second, 360° pose estimation is presented, in which the pose of a robot at all locations is estimated. Third, a 360° localization application is integrated with a closed‐loop real‐time trajectory tracking controller. The successful results of simulations and real experiments of trajectory tracking are also presented.